1981
DOI: 10.1007/bf01976985
|View full text |Cite
|
Sign up to set email alerts
|

The effect of growing beans together with maize on the incidence of bean diseases and pests

Abstract: Compared with mono-cultures, beans grown in association with maize showed generally less incidence of the following diseases and pests: halo blight, bean common mosaic, anthracnose, common blight, scab, Phoma, mildew, bolworm and to a lesser extent angular leaf spot. For white mold and the black beetle Systates the opposite was observed. Rust and aphids were erratic in this respect.Apparently a kind of cultural control of the major bean diseases in Kenya is effected by growing beans in association with maize.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 2 publications
(1 reference statement)
0
19
0
Order By: Relevance
“…In some circumstances, maize in particular may decrease rust levels, possibly due to the provision of a physical barrier influencing factors such as spore dispersal and temperature (Msuku and Edje 1982;Sengooba 1990;Boudreau and Mundt 1992;Fininsa 1996). However, ambiguous results have also been obtained (Van Rheenen et al 1981;Boudreau and Mundt 1992) and in some studies, such as reported by Diaz (1981), an increase in rust incidence was observed for beans in association with maize. These differences may be due to variation in topography, wind patterns, and other local factors influencing microclimate and spore dispersal.…”
Section: Biological Control and Induced (Acquired) Resistancementioning
confidence: 70%
See 3 more Smart Citations
“…In some circumstances, maize in particular may decrease rust levels, possibly due to the provision of a physical barrier influencing factors such as spore dispersal and temperature (Msuku and Edje 1982;Sengooba 1990;Boudreau and Mundt 1992;Fininsa 1996). However, ambiguous results have also been obtained (Van Rheenen et al 1981;Boudreau and Mundt 1992) and in some studies, such as reported by Diaz (1981), an increase in rust incidence was observed for beans in association with maize. These differences may be due to variation in topography, wind patterns, and other local factors influencing microclimate and spore dispersal.…”
Section: Biological Control and Induced (Acquired) Resistancementioning
confidence: 70%
“…Panse et al (1997) obtained slight increases in yield using various mixture combinations. Other authors, however, reported an inconsistent effect of mixtures on rust as compared to monoculture (Van Rheenen et al 1981;Aylor 1988), although the general tendency does appear to be a lessening of the amount of disease.…”
Section: Biological Control and Induced (Acquired) Resistancementioning
confidence: 91%
See 2 more Smart Citations
“…Legume intercrops are a potential source of plant nutrients that compliment/supplement inorganic fert ilizers [17]. Legu me intercrops have several socioeconomic [18], and biological and ecological [19,20,21,22,23] advantages compared to sole cropping for small-holder farmers [24]. In addition, certain legumes crops provide food to humans and livestock [17].…”
Section: Introductionmentioning
confidence: 99%